Komunitas Online Sebagai Ruang Aman: Penguatan Self-Esteem dan Emosi Positif Anak Broken Home Melalui Konseling Komunitas - Widyaningrum, Firda Rinda; Apriliana, Nabila Shinta; Putri, Dinda Pangestika Setya; M, Muslikah; Mahfud, Ashari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The phenomenon of broken homes in Indonesia shows an increasingly complex tendency. Not only caused by divorce, broken home conditions can also arise due to disharmony in family relationships, domestic violence, emotional neglect, and dysfunction of parental roles. This situation has a serious impact on children’s psychosocial development, especially in terms of the formation of self-esteem and the ability to manage positive emotions. This article aims to examine the role of online communities as safe spaces in strengthening self-esteem and positive emotions of broken home children through a community counseling approach. The focus of the discussion includes the dynamics of emotional needs of broken home children, characteristics of supportive online communities, and community-based counseling strategies in a digital context. The method used in this study is a literature review. The results of the study show that online communities that have the principles of inclusivity, empathy, and openness can be an effective means of meeting the emotional support needs of broken home children. Positive interactions in the community contribute to strengthening self-esteem and the development of positive emotions, such as feeling safe, accepted, and appreciated. Broken home communities in the digital realm, as carried out by Behome.id through programs such as Jumat Sambat, Teman Curhat (ManCur), DIALOG (Diskusi Sama Psikolog), These programs play an important role in facilitating open discussions, self-reflection, and empowering members to overcome emotional trauma, and strengthen social support among broken home teenagers. The conclusion of this study shows that well-managed online communities have the potential to become strategic safe spaces to support the psychological development of broken home children and expand the scope of community counseling practices in the digital era.